Instituting the Common in the Artistic Circulation: From Entrepreneurship of the Self to Entrepreneurship of the Multitude - Szreder, Kuba (Praktyka Teoretyczna, 2018)
In this paper I trace the contradictions embedded in global artistic circulation, which is dialectically analysed as a nexus of exploitation and a site where the commons can be instituted. To enable this argument, I synthesise the methodologies of dialectical materialism, the sociology of art and action research, supplementing a theoretical overview of systemic pressures with a keen observation of the social practices that emerge in critical response to it. Basing my analysis on empirical evidence, I examine social conflicts, triggered by the extracting value from the distributed labour of artistic networks, as political opportunities to be seized by progressive art workers. Thus, I propose a new perspective on current processes of incorporating contemporary art into the late-capitalist cycles of accumulation and modes of establishing and reproducing social distinctions. Instead of mourning for – presumably lost but still positively valorised – artistic autonomy, I argue for a revamping of the apparatuses regulating artistic circulation for the sake of the labouring multitudes.